2020
DOI: 10.3390/genes11121459
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Multiple Gene Variants with Ageing Skeletal Muscle Phenotypes in Elderly Women

Abstract: There is a scarcity of studies that have investigated the role of multiple single nucleotide polymorphisms (SNPs) on a range of muscle phenotypes in an elderly population. The present study investigated the possible association of 24 SNPs with skeletal muscle phenotypes in 307 elderly Caucasian women (aged 60–91 years, 66.3 ± 11.3 kg). Skeletal muscle phenotypes included biceps brachii thickness, vastus lateralis cross-sectional areas, maximal hand grip strength, isometric knee extension and elbow flexion torq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 122 publications
0
15
0
1
Order By: Relevance
“…MVC EF and MVC KE were measured with a custom-built dynamometer. The detailed process for the muscle strength measurements are described in our previous work [ 38 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…MVC EF and MVC KE were measured with a custom-built dynamometer. The detailed process for the muscle strength measurements are described in our previous work [ 38 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that there is a significant association between genotype and skeletal muscle phenotype. For example, the presence of SNPs is associated with better skeletal muscle strength performance (Khanal et al, 2020). We selected the 23 SNPs included in this study were all focused on genes related to skeletal strength, to further study the genetic composition and phylogeny of the five ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrasound (MyLab ™ Twice, Esaote Biomedical, Italy) was used to perform the scan to measure the biceps brachii thickness at 60% length from the proximal end of the humerus [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%